Caregiver Quality of Life During Pediatric Influenza-Like Illness: A Cross-Sectional Study During the COVID-19 Pandemic - Kevin M Overmann MD, MS; Stephen C Porter MD, MPH, MSc; Yin Zhang MS; Maria T Britto MD, MPH (Journal of Patient Experience, 2023)
The objective of this study was to quantify the quality of life (QoL) of caregivers with children with influenza-like illnesses (ILI) and to identify factors associated with worse QoL. This was a cross-sectional cohort study of caregivers in a pediatric emergency department with previously healthy young children with ILI. The primary outcome was caregiver QoL. Additional measures included health literacy, social support, and caregiver health status. Two hundred and eighty-one caregivers completed the study. And 41% reported overall QoL was worse during their child's illness. The median QoL score was 3.8 [3.1, 4.6] in a 7-point scale. Illness duration was associated with worse overall QoL score (0.128 worse for each additional day of illness). The median emotions domain score was 2.5 [1.5, 4.0], the worst of any domain. Caregivers who perceived worse illness severity had lower emotions domain scores (2.61 vs 6.00, P  = .0269). Caregivers with adequate literacy had lower mean QoL scores (3.08 vs 4.44, P  < .0001). Childhood illnesses worsen caregiver QoL. Factors associated with worse QoL were perception of illness severity and duration. Addressing caregiver QoL could mitigate the impact of childhood acute illnesses on caregiver wellbeing.